Exploration of the Integration Paths between “Aesthetic Education” and “Ideological and Political Education” in Universities under the Background of New Liberal Arts Construction — A Case Study of Humanities and Social Sciences Majors - Wang, Lele; Zhang, Muyue (Journal of Theory and Practice in Humanities and Social Sciences, 2024)
Based on the background of new liberal arts construction, this paper takes humanities and social sciences majors as the research object and systematically explores the in-depth integration path of art education and ideological and political education. From the dual perspectives of theoretical logic and practical value, the paper first points out that the two are consistent in goals and complementary in content under the fundamental task of "strengthening moral education and cultivating people": art education provides an effective carrier for ideological and political education with its vividness and emotionality, while ideological and political education injects ideological connotation and value orientation into art education. Secondly, the paper analyzes the problems existing in the current integration practice, such as vague goals, disconnected content, single path and insufficient teaching staff. On this basis, it proposes to construct a "trinity curriculum + multi-dimensional linkage practice" system. This is achieved by excavating the "art-ideological and political" elements in professional courses, developing interdisciplinary courses, implementing joint teaching, and carrying out situational practice in combination with on-campus, off-campus and online platforms. At the same time, it emphasizes the need to build an interdisciplinary teaching team and establish a scientific and diversified evaluation mechanism to ensure the effectiveness of integration. This paper aims to provide theoretical reference and practical paths for enhancing the effectiveness of ideological and political education, enriching the connotation of art education, and realizing the comprehensive educational goals of "educating people with aesthetics, nurturing people with culture, and cultivating people with morality".